TRAINING BOBATH METHODS BETTER THAN FELDENKRAIS METHODS TO IMPROVE OF BALANCE AMONG POST STROKE PATIENTS - Aditya Denny Pratama (Jurnal Vokasi Indonesia, 2017)
Stroke is a disease affecting of brain that causes suddenly neurological dysfunction. Stroke can cause damage to brain tissue and clinically in a relatively long period of time and is the most common cause of physical disability such as decreased in the balance. This study aims to determine how much of an increase balance in patients with post stroke after being given Bobath training and Feldenkrais training. This study was an experimental with pretest-posttest group design conducted at Sasana Husada Stroke service and Karmel Stroke Service, in March-April 2015. This study used 14 subject of post stroke patients randomly divided into two groups. Group 1 was given Bobathtraining and group 2 was given Feldenkrais training. Both groups were given training 3 times a week for total 8 weeks. The balance test measured by Brunel Balance Assessment (BBA) instrument.The results showed that in group I there was an increasing balance of 4.71 ± 1.11 to 9.57 ± 1.72, while in group II was also an increase in balance of 4,71 ± 0,95 to 5.57 ± 0.98. Based on statistical tests, there is a significan increase of balance in group I and II after training. And training in group I was better than group II in improvement of balance among post stroke patient (p < 0.05).It can be conclusion that the training Bobath method is better thanFeldenkrais method to increase the balance of post stroke patients. Keyword; Stroke, Balance, BBA, Bobath, Feldenkrais